Keanekaragaman Jenis Fauna Amphibia di Taman Nasional Lore Lindu - Annawaty Annawaty; Paserang Asri Pirade (Biology Department, Mathematics and natural science, Tadulako University, 2009)
The aim of this research was to know the diversity of amphibians in Lore Lindu National Park. The research was used survey methods which was located at the conservation area of Kulawi section in the Lore Lindu National Park Central Sulawesi. The result of the research showed that there were five (5) species of amphibians collected which were found and belonged order Anura. These species were Bufo melanostictus, Bufo celebensis, Fejervarya cancrivora, Rana (Hylarana) erythraea, and Kaloula baleata Muller.